Misoprostol versus prostaglandin E2 gel for labor induction in premature rupture of membranes after 34 weeks of pregnancy. Issue 3 (September 2015) - Zhang, Yan; Wang, Jun; Yu, Yan; Xie, Cui; Xiao, Meiqun; Ren, Lirong
Abstract Background Both misoprostol and prostaglandin E2 (PGE2) gel are used for labor induction in women with premature rupture of membranes (PROM). Objectives To evaluate studies comparing the effects of misoprostol and PGE2 gel in labor induction. Search strategy Databases including Medline, Embase, and the Cochrane Central Register of Controlled Trials were searched for relevant papers. Selection criteria Randomized controlled trials comparing the use of misoprostol and PGE2 gel for labor induction in women with PROM were included. Data collection and analysis For meta-analyses, the Mantel–Haenszel method was used for dichotomous data, and the inverse variance method was used for continuous data. Main results Four randomized controlled studies (n = 615) were included. There were no significant differences between the two groups in the induction-to-delivery interval (mean difference – 4.44 hours; 95% confidence interval [CI] –9.35 to 0.48), rate of cesarean delivery (odds ratio [OR] 0.90; 95% CI 0.44–1.85), and rate of neonatal intensive care unit admission (OR 0.89; 95% CI 0.57–1.38). Women receiving misoprostol had a significantly higher rate of tachysystole than did those receiving PGE2 gel (OR 4.84; 95% CI 2.46–9.54). Conclusions Misoprostol is as efficacious and safe as PGE2 gel for labor induction in women with PROM.